The missing ingredient: rethinking the drought disaster risk reduction and climate change adaptation nexus in Chirumhanzu District, Zimbabwe - Grey, Mashoko Stephen (Rhodes University, Faculty of Science, Department of Environmental Science, 2018)
Two of the main challenges facing communities and governments in developing countries are the reduction of risks of hydro-meteorological hazards and adaptation to climate change. As climate variability and change impacts are becoming more visible in the form of disasters, and are negatively affecting climate sensitive livelihoods and eroding communities' ability to fully recover, leading to increased vulnerability to subsequent climate risks. The unpredictability of current weather systems, therefore, makes it very difficult for poor governments and households to deal with adverse impacts of climate change. Furthermore, the fragmented approach to DRR and CCA with regards to practice, policy and organisational frameworks for dealing with climate risks is resulting in coordination challenges for the government departments. This study aimed to explore how local households and communities perceive and are experiencing and coping with climate change and drought, and what that means for integrating hydro-meteorological disaster risk reduction and climate change adaptation. The study was carried out in Chirumhanzu district and the methods used for data collection included: 217 household surveys; six focus group discussions; participatory learning actions methods; key informant's interviews and document review. The majority of households owned low value material assets and had low levels of livelihood capitals and this exposed them to the impacts of climate variability and successive droughts. This low adaptive capacity largely affected their ability to engage effective drought risk reduction and adaptation strategies for their livelihood activities in small-scale farming and livestock rearing. Vulnerability to climate risks was exacerbated by seasonal weather forecasts, which were deemed by some households to be unreliable, inaccurate and not easily understood, while others used of indigenous knowledge. Successive droughts affected households' access to food and cash income for other household demands. Other non-climatic factors that contributed to adverse drought impacts at the household level were an emphasis on reactive humanitarian aid approach and the poor economy in Zimbabwe. Additionally, the policy framework for dealing with climate change and drought hazards is fragmented and weak; and is housed in different government departments making it difficult to coordinate and implement. To improve climate risk management, there is need for the government to appreciate that drought risk reduction and climate change adaptation are all about reducing vulnerability. Understanding this, might assist in improving government focus on addressing the underlying causes of vulnerability and mainstreaming DRR and CCA into development processes through addressing specific and generic adaptive capacities. The thesis argues that as long as rural households are involved in climate sensitive livelihood activities and not getting meaningful intervention to diversity and/or better intensify their livelihood activities, they will continue to be vulnerable to successive climate risks. This fragmented approach to dealing with climate risks, is not yielding any successful results with regards to building resilience, risk reduction or adaptation of rural households.
Keywords: Climatic changes -- Zimbabwe -- Chirumanzu District; Climatic changes -- Government policy -- Zimbabwe -- Chirumanzu District; Climatic changes -- Economic aspects -- Zimbabwe -- Chirumanzu District; Natural disasters -- Risk assessment -- Zimbabwe -- Chirumanzu District; Drought management -- Zimbabwe -- Chirumanzu District; Hazard mitigation -- Zimbabwe -- Chirumanzu District